Combining Savage and Laplace: a new approach to ambiguity - Ralf Diedrich (Theory and Decision, 2024)
Abstract This paper presents a new representation of preference orderings for the study of ambiguity-related decision-making. The central feature is a preference-based decomposition of subjective probabilities that provides information about inherent ambiguity. The probability decomposition is combined with a utility function reflecting the decision-maker's attitude toward ambiguity. The proposed theory generalizes Savage's SEU and allows for a straightforward measurement of ambiguity and ambiguity aversion while keeping concepts for measuring risk and risk attitudes unaffected. For the measurement of ambiguity, concepts of probability theory can be used since decision acts can be interpreted as two-dimensional probability distributions. The proposed measure of ambiguity aversion exploits the properties of the utility function in the same way as the Arrow/Pratt measure of risk aversion.
Additional information: D81
Keywords: 330; Ambiguity; Knightian uncertainty; Subjective probability; Ambiguity aversion